Personality and Social Framing in Privacy Decision-Making: A Study on Cookie Acceptance - Coventry, Lynne M.; Jeske, Debora; Blythe, John M.; Turland, James; Briggs, Pam (Frontiers in Psychology, 2016)
Despite their best intentions, people struggle with the realities of privacy protection and will often sacrifice privacy for convenience in their online activities. Individuals show systematic, personality dependent differences in their privacy decision making, which makes it interesting for those who seek to design ‘nudges’ designed to manipulate privacy behaviors. We explore such effects in a cookie decision task. Two hundred and ninety participants were given an incidental website review task that masked the true aim of the study. At the task outset, they were asked whether they wanted to accept a cookie in a message that either contained a social framing ’nudge’ (they were told that either a majority or a minority of users like themselves had accepted the cookie) or contained no information about social norms (control). At the end of the task, participants were asked to complete a range of personality assessments (impulsivity, risk-taking, willingness to self-disclose and sociability). We found social framing to be an effective behavioral nudge, reducing cookie acceptance in the minority social norm condition. Further, we found personality effects such that those scoring highly on risk-taking and impulsivity were significantly more likely to accept the cookie. Finally, we found that the application of a social nudge could attenuate the personality effects of impulsivity and risk-taking. We explore the implications for those working in the privacy-by-design space.